2011
DOI: 10.1542/peds.2011-1712
|View full text |Cite
|
Sign up to set email alerts
|

Infant Sleep After Immunization: Randomized Controlled Trial of Prophylactic Acetaminophen

Abstract: WHAT'S KNOWN ON THIS SUBJECT:For adults, sleep deprivation before or after immunization is associated with decreased antigen-specific antibody formation, but little is known about infant sleep before and after immunization or the effects of prophylactic acetaminophen treatment on infant sleep. WHAT THIS STUDY ADDS:Infants demonstrated increased sleep duration in the 24 hours after immunization, particularly if they were immunized after 1:30 PM and had elevated temperatures. Acetaminophen use was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
1
Order By: Relevance
“…Besides these, the findings of another RCT [24] reporting about the infant sleep after immunization and relation of acetaminophen (paracetamol) use need mention here. This RCT found that paracetamol use post-immunization (not prophylactic) was associated with increase in the infant sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these, the findings of another RCT [24] reporting about the infant sleep after immunization and relation of acetaminophen (paracetamol) use need mention here. This RCT found that paracetamol use post-immunization (not prophylactic) was associated with increase in the infant sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in New York City and Kansas in USA have revealed a wide support and acceptability for text messages / short message service (SMS) as a mode of immunization reminder/recall [ 20 23 ]. Also, person to person telephone reminders has also been found to be preferred by parents in studies in Nigeria and USA [ 18 , 24 ]. It is possible that mothers who preferred cellphone call reminders in this study may have done so because they are likely to have the opportunity to express themselves if they plan to attend their children schedule immunization clinic or request to change appointment date if they cannot attend for any reason [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, maternal age was not a significant predictor of preference for cell phone calls or SMS in the current study. However, findings from previous study in USA showed that parents aged 30 years and above preferred e-mail for reminder [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supangat et al ( 29 ) reported that sleepiness was the second most common systemic effect among Indonesian medical clerkship students after receiving the CoronaVac vaccine. Another study by Franck et al ( 30 ) found that sleep duration in the first 24 h after immunization was increased. Hendarto et al ( 31 ) and Rachman et al ( 32 ) found that feeling hungry is one of the AEFI symptoms reported by Indonesian CoronaVac recipients.…”
Section: Discussionmentioning
confidence: 94%